Replacement of fish oil with a DHA-rich algal meal derived from Schizochytrium sp. on the fatty acid and persistent organic pollutant levels in diets and flesh of Atlantic salmon (Salmo salar, L.) post-smolts. (15th October 2015) - Sprague, M.; Walton, J.; Campbell, P.J.; Strachan, F.; Dick, J.R.; Bell, J.G.
Highlights: A DHA-rich algal product was tested as a replacement for fish oil in salmon feeds. Algal diets contained the lowest POP levels and were reflected in the flesh. Fish fed higher dietary algal inclusion had similar DHA levels to fish oil fed fish. Lack of EPA in algal diets compromised the final nutritional value to the consumer. Abstract: The replacement of fish oil (FO) with a DHA-rich Schizochytrium sp. algal meal (AM) at two inclusion levels (11% and 5.5% of diet) was tested in Atlantic salmon post-smolts compared to fish fed a FO diet of northern (NFO) or southern hemisphere (SFO) origin. Fish were preconditioned prior to the 19-week experimental feeding period to reduce long-chain polyunsaturated fatty acid (LC-PUFA) and persistent organic pollutant levels (POPs). Dietary POP levels differed significantly between treatments in the order of NFO > SFO > 11AM/5.5AM and were subsequently reflected in the flesh. Fish fed the 11AM diet contained similar DHA levels (g 100 g −1 flesh) to FO-fed fish, despite percentage differences. However, the low levels of EPA in the diets and flesh of algal-fed fish compromised the overall nutritional value to the final consumer. Nevertheless, further developments in microalgae culture offer a promising alternative lipid source of LC-PUFA to FO in salmon feeds that warrants further investigation.